Edukasi Mengenali Tanda dan Gejala ISK Pada Masyarakat Lansia di Kelurahan Sukabakti, Kecamatan Curug, Kabupaten Tangerang - Effendi, Ida; Bella, Isa; Samira, Jihan; Devita, Arleen; Prasetyaningsih, Noviani (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
The elderly population in Indonesia is increasing. Data shows that around 1 in 10 residents are elderly. The productive elderly (potential elderly) can still contribute to the country's progress. Health problems are important to support in all aspects of the elderly. Urinary tract infections (UTI) attack people of all ages. It is known that UTIs in elderly people in Indonesia are increasing. Predisposing factors for UTI sufferers in the elderly include comorbid diseases such as diabetes mellitus, malnutrition, cognitive dysfunction, depression, functional status disorders, prostatitis, history of surgery and vaginal prolapse, and lack of water consumption. Some urinary tract infections (UTIs) can be prevented by recognizing the early signs and symptoms of the disease and practicing clean and healthy living. If it occurs, urinary tract infections cause distress, disrupt daily activities and can increase the number of hospital admissions. Knowledge of recognizing the specific symptoms and signs of urinary tract infections will determine early detection and early diagnosis of this disease. Therefore, community service activities are carried out for the elderly community through education and counseling to recognize the signs and symptoms of urinary tract infections as prevention so that they can improve the health status of the elderly community. Through this activity, it is also hoped that the elderly community will receive more attention to their health through promotive, preventive and curative actions and become potential elderly people.